An Introduction to Content Analysis of Critical Papers Related to Iran's Political-Social Issues - Qolamreza Mohammadi Mehr; Majid Tavassoli Rokn Abadi (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
This article analyzed critical papers related to the political-social issues of Iran. The purpose of the research was to identify the observance level of the fundamentals of criticism and scientific evaluation in critical papers. The method was content analysis, and the statistical population consisted of 123 articles, all critical texts published in various sources over the past three decades and available to researchers. Findings of the research showed that in 56.7% of the critical papers both the strengths and weaknesses of the works have been considered, and in the rest of the papers, only strengths or weaknesses have been considered. Also, in 65.8 percent of the papers, it is focused on the author's critique (positive or negative). In addition, only 14.2% of the papers have been provided with suggestions and solutions to address the shortcomings of the studies. Accordingly, it should be argued that there is still a long way to follow the rules of scientific critique and impartiality and avoidance of biased judgments in the criticism of books related to the political-social changes in Iran and the criticism of other works.